Estimation of Super High-Rise Pumping Pressure for High-Performance Concrete Based on Computational Fluid Dynamics Modeling and Situation Measurement - Weijiu Cui; Chuankai Zhao; Sheng Wang (Advances in Civil Engineering)
Traditional methods fail to predict the pumping pressure loss of high-performance concrete properly in super high-rise pumping situations due to complex changes of concrete properties. Therefore, it is imperative to propose a relative accurate method for pumping pressure estimation in super high-rise buildings. This paper builds the simplified pressure calculation method “pressure induced by the gravity plus pressure along the pipe line.” The later one is gained by establishing topology optimized model based on computational fluid dynamics and considering the lubrication layer formation. The effect of rheological properties and flow rate is analyzed based on this model in detail. Furthermore, the developed calculation method is verified by the measured pumping pressure during the super high-rise building construction of the Shanghai Tower (the tallest building in China recently). The relative differences between the calculation results and the measured data in situ are less than 6%, indicating the applicability of this method for predicting the pressure loss of the super high-rise pumping.